Anglo-American Multinationals in Europe: The Curious Case of Hudson’s Bay Company Taking over Galeria Kaufhof - Gebert, Raoul (Relations industrielles / Industrial Relations, 2019)
Multinational corporations are undeniably the driving force of globalization and regional economic integration. A convenient institutional framework (Hall and Soskice, 2001) to apply when comparing multinationals from different host countries is the well-travelled road of dividing capitalist economies into coordinated market economies (CMEs) and liberal market economies (LMEs). This article aims to elucidate the tensions between centralized human resources practices and labour union avoidance usually exhibited by multinationals from so-called Liberal Market Economies (LMEs) when they expand into coordinated ones (CMEs). Specifically, it examines the recent acquisition of the German retail giant Galeria Kaufhof by the Canadian multinational Hudson’s Bay Company (HBC). The article shows that HBC has settled into an uneasy acceptance of the CME institutions, while its investment motives vacillate between a long-term, market-enlargement strategy and a short- to medium-term one, based on the rapidly increasing real estate value of its downtown flagship stores. The article encourages researchers in IR to retain three principal conclusions for the literature and for further study. First, without predetermining outcomes by looking at host-country or home-country effects alone, institutionalist frameworks do present a convenient backdrop for conceptualizing movements of multinationals across jurisdictions. Secondly, concepts such as bricolage, recombining of institutional elements and institutional entrepreneurship, stemming from the institutional change literature, should routinely figure in one’s analytical toolbox, in any attempt at non-deterministic institutional analysis. Finally, sector-level actors, such as trade unions and employers’ associations, can play an essential role in any successful adaptation of collective bargaining institutions in the context of globalization by developing, maintaining and carefully utilizing their repertoire of strategic capabilities.
Keywords: asociación de empleadores; associations d’employeurs; capacidades estratégicas; capacités stratégiques; employers’ associations; institucionalismo; institutionalism; institutionnalisme; multinacionales; multinationales; multinationals; sindicatos; strategic capabilities; syndicats; trade unions

The Pitfalls and Promises of Successfully Organizing Foodora Couriers in Toronto - Gebert, Raoul (A Modern Guide To Labour and the Platform Economy, 2021)
Gig economy workers, particularly those on platforms such as Foodora and UBER, do not have a clear legal status in Canada, and unionization has largely escaped them. One obstacle is that union certification presupposes a stable employment relationship and a relatively fixed workplace. It does not lend itself easily to a decentralized organization of work, let alone one that is merely "facilitated" by a digital platform. Another obstacle is their dual status of being extremely dependent on the platform for everything from payments to scheduling, while being legally considered as "independent contractors." In response, Canadian labour unions have pushed tribunals to adopt a new legal status: that of "dependent contractors." Based on the successful unionization drive among Foodora couriers in Toronto in 2020, our contribution argues that the involved actors resorted to "institutional experimentation" to open traditional frameworks of collective bargaining and labour law to workers of the gig economy.
https://www.researchgate.net/publication/355832465_The_pitfalls_and_promises_of_successfully_organizing_Foodora_couriers_in_Toronto